Development of device CAP-10 to perform inprocess testing of the single-core wire capacitance per unit length; International Journal of Systems Applications, Engineering & Development; Vol. 10 - Goldstein (Goldshtein) A. E. Aleksandr Efremovich (2016, 2016)
Title screen